A comparison of ultrasound-guided high intensity focused ultrasound for the treatment of uterine fibroids in patients with an anteverted uterus and a retroverted uterus. (17th August 2016) - Zhang, Wenyi; He, Min; Huang, Guohua; He, Jia
Abstract: Objective: The aim of this study was to compare the treatment outcomes of ultrasound-guided high-intensity focused ultrasound (USgHIFU) for uterine fibroids in patients with an anteverted uterus versus a retroverted uterus. Materials and methods: Based on the principles of statistics we enrolled 221patients with an anteverted uterus and 221 with a retroverted uterus. All patients had a solitary uterine fibroid and every fibroid was identified as hypointense on the T2 weighted images (T2WI) on magnetic resonance. The baseline characteristics of the patients, treatment results and adverse events were compared between the two groups. Results: There were no significant differences in baseline characteristics between the two groups. The average non-perfused volume ratio of fibroids was 85.2 ± 18.7% in the group of patients with a retroverted uterus, while it was 87.7 ± 11.8% in patients with an anteverted uterus ( P  < 0.05). The fibroids in patients with a retroverted uterus were treated using lower sonication power and longer sonication time. During the procedure patients with a retroverted uterus had a higher incidence of sciatic/buttock pain and groin pain, while patients with an anteverted uterus complained of lower abdominal pain or a burning sensation on the skin. Immediately after USgHIFU, the rates of sciatic/buttock pain and skin burn were significantly higher in patients with a retroverted uterus. Conclusion: The results of this study indicated that uterine fibroids with hypointensity on T2WI in a retroverted uterus can be safely and effectively treated with USgHIFU. However, the fibroids in an anteverted uterus are easier to treat with USgHIFU.